Potential categories of perceived recurrence risk in stroke patients and their relationship with self-management ability - Wu, Yihao; Gong, Shitong; Long, Fei; Yin, Jie (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to identify latent profile categories of recurrence risk perception among stroke patients, analyze the factors influencing these categories, and examine their correlation with self-management ability. The findings are intended to provide new insights and a foundation for enhancing self-management in stroke patients.MethodsA total of 221 stroke patients admitted to the Department of Neurology and Neurosurgery at Xuzhou Central Hospital between January 2024 and December 2024 were selected using a convenience sampling method. Data were collected using a general information questionnaire, the Stroke Patient Recurrence Risk Perception Assessment Scale, and the Stroke Patient Self-Management Ability Assessment Scale. Statistical analyses included factor analysis and pairwise comparisons to examine influencing factors and their relationships.ResultsA total of 221 questionnaires were distributed, with 23 invalid responses excluded, yielding an effective response rate of 89.59%. The mean recurrence risk perception score was 39.63 ± 5.67, while the mean self-management ability score was 85.69 ± 12.33. Latent profile analysis identified three distinct categories of recurrence risk perception: high -level, medium -level, and low -level risk perception groups. Univariate analysis revealed significant differences in recurrence risk perception based on age (χ2 = 11.132, p = 0.025), education level (χ2 = 5.523, p = 0.044), living environment (χ2 = 9.868, p = 0.007), disease duration (χ2 = 13.142, p = 0.011), and stroke frequency (χ2 = 25.710, p < 0.001). Logistic regression analysis indicated that age, living environment, disease duration, and stroke frequency were protective factors for recurrence risk perception (OR < 1, p < 0.05). Pairwise comparisons showed that patients in the high -level risk perception group exhibited significantly higher self-management ability compared to those in the medium -level (p < 0.01) and low -level risk perception groups (p < 0.01). Similarly, patients in the medium -level risk perception group demonstrated greater self-management ability than those in the low -level risk perception group (p < 0.01).ConclusionThis study utilized latent profile analysis to classify stroke patients’ recurrence risk perception into three categories: high, medium, and low. These profiles were influenced by age, living environment, disease duration, and stroke frequency. Moreover, recurrence risk perception was significantly associated with self-management ability. Clinical practitioners should focus on patients in the low -level risk perception group, implementing targeted interventions to enhance their awareness of recurrence risk, thereby improving self-management, preventing recurrence, and optimizing patient outcomes.